Audit and feedback is an effective implementation strategy to increase fidelity to a multi-component labor induction protocol designed to reduce obstetric inequities - Rebecca F. Hamm; Sreya Pattipati; Lisa D. Levine; Samuel Parry; Sindhu K. Srinivas; Rinad S. Beidas (Implementation Science Communications)
Abstract Background Studies have demonstrated that standardizing labor induction (IOL), often with the use of protocols, may reduce racial inequities in obstetrics. IOL protocols are complex, multi-component interventions. To target identified implementation barriers, audit and feedback (A&F) was selected as an implementation strategy. Here, we aimed to understand the acceptability and effect of A&F on fidelity to this complex intervention through quantitative and qualitative approaches. Methods This secondary analysis of a type I hybrid effectiveness-implementation trial (10/2018–12/2022) compared 2 years before (PRE) to 2 years after (POST) implementation of an IOL protocol at two sites. Fidelity to each of 8 specific protocol components was collected via chart review. During the POST period, unit-aggregated A&F reports were distributed via email every 3 months to site clinicians. Reports tracked fidelity to protocol components over time. For this analysis, we compared component fidelity PRE to POST-implementation. Additionally, during the POST period, we compared fidelity by month after each A&F (Month#1 v. Month#2/3) to evaluate the effect of A&F over time. Acceptability of A&F reports was evaluated using qualitative interviews. Results 8509 labor inductions were included (PRE = 4214, POST = 4295). A&F reports were successfully distributed every 3 months for the 2-year POST period. PRE to POST-implementation, fidelity to 4 of the 8 components increased significantly (cervical Foley utilization, latent labor examination frequency, amniotomy timing, and intrauterine pressure catheter utilization), without change in the other 4 components. For 2 of those 4 components where improvement was noted, there was no difference in fidelity by month after A&F report; rather, there was sustained improvement across the POST-implementation period. On the other hand, for the remaining 2 components, fidelity peaked in the first month after each A&F report, with some decline in the following 2 months prior to the next A&F report. Qualitative analysis (n = 24) supported A&F acceptability, with A&F described as “motivating” and “helpful.” Conclusions A&F was an effective implementation strategy to promote fidelity to certain components of this labor induction protocol. With some decline in effect after the first month POST-A&F report, increased A&F frequency should be considered in future work targeting obstetric outcomes, as well as health inequities.